THE EFFECT OF USING MNEMONIC TECHNIQUE TOWARD STUDENTS’ VOCABULARY MASTERY AT GRADE XII-SCIENCE STUDENTS OF SMAN 9 KOTA BENGKULU - LIZA OKTARINI; BAMBANG SUWARNO; I WAYAN Dharmayana (Universitas Bengkulu, 2017)
This study aimed to find out whether the use of Mnemonic technique affected the students’ vocabulary mastery. This study employed a quasi experimental design. The subject of this study comprised 64 students of grade XII science class of SMAN 9 Kota Bengkulu. The instrument of this study was a vocabulary test. The experiment class was taught by Mnemonic technique, while the control class by contextual learning. In the pre test there was no significant difference in mastery between the experiment class (mean=71,18) and control class (mean=68) with t count (0,1)< t table (df=62 sig 0,05). After the use of Mnemonic technique, in the post test, there was a significant difference in mastery between the experiment class (mean=73,51) and control class (mean=67,53), with tcount (1,99) > t table (1,67), (df=62; sig. 0,05). It can be concuded that the use of Mnemonic technique was effective toward the students’ vocabulary mastery at grade XII-Science Students of SMAN 9 Kota Bengkulu.